High-strength fuel pellets made of flour milling and coal slack wastes; Energy; Vol. 243 - Tabakaev R. B. Roman Borisovich; Kan V. V. Viktor Vladimirovich; Dubinin Yu. V. Yury Vladimirovich; Rudmin M. A. Maksim Andreevich; Yazykov N. A. Nikolay Alekseevich; Skugarov A. O. Artem Olegovich; Alekseenko E. V. Eduard Vladimirovich; Zavorin A. S. Aleksandr Sergeevich; Preys S. V. Sergey Valentinovich (2022, 2022)
Title screen